Taxonomy and biogeography of the freshwater crabs of Tanzania, East Africa (Brachyura: Potamoidea: Potamonautidae, Platythelphusidae, Deckeniidae) - Reed, Sadie K.; Cumberlidge, Neil (Zootaxa, 2006)
The taxonomy of the freshwater crabs of Tanzania, East Africa is revised based on a large collection of previously unreported material. The crabs are treated here as a distinct regional subset of the African continental fauna. We recognize 25 species belonging to three genera (Potamonautes MacLeay, 1838, Platythelphusa A. Milne-Edwards, 1872, and Deckenia Hilgendorf, 1869a) and three families (the Potamonautidae Bott, 1970, the Platythelphusidae Colosi, 1920, and the Deckeniidae Ortmann, 1897). Tanzania is home to fourteen species of Potamonautes (including one new species), 9 species of Platythelphusa and 2 species of Deckenia. These estimates can be expected to change as the taxonomy of the freshwater crabs of this region becomes more refined. Potamonautes unisulcatus (Rathbun, 1933) is removed from synonymy and is recognized as a valid species; P. platycentron (Hilgendorf, 1897), originally a subspecies of P. johnstoni (Miers, 1885), is regarded as a valid species; P. ambiguus (Rathbun, 1904) is treated here as a junior subjective synonym of P. johnstoni (Miers, 1885), and P. johnstoni stappersi (Balss, 1936) is treated as a junior subjective synonym of P. loveridgei (Rathbun, 1933). The present work adds another species of Potamonautes, P. xiphoidus n. sp. from Tanzania. A number of morphological characters (including the shape and size of the dorsal membrane of gonopod 1) are identified to help clarify the taxonomy of Potamonautes in Tanzania. A revised species list for Tanzania is provided, as well as updated identification keys to the families, genera and species of Tanzanian freshwater crabs. The distribution of each species is refined based on new localities. Three out of 25 species (12.5%) (P. infravallatus, P. unisulcatus and P. xiphoidus) are endemic to Tanzania, but this number rises to 13 out of 25 (52%) if the Lake Tanganyika endemic species which occur in other countries that border the lake are included. Only two of the 25 Tanzanian species of freshwater crabs (P. lirrangensis and P. suprasulcatus) occur outside of the East African region in the D. R. Congo and Malawi.